79 Adapting a small bedside teaching programme to support paediatric trainees through the new COVID-modified MRCPCH virtual clinical exam. (17th August 2022) - Ryan, Aoife; Edwards, Gemma
Abstract : Aims: Objective: timely provision of an accessible virtual teaching programme for paediatric trainees to supplement their preparation for the new remote MRCPCH clinical exam format. Background: membership to the Royal College of Paediatrics and Child Health (MRCPCH) is attained following successful completion of both theory and clinical components of the RCPCH-led examinations. Based on an OSCE-style structure, practical exam candidates rotate through various stations assessing different clinical and communication skills. During the COVID-19 pandemic the standard exam format was modified to facilitate ongoing trainee assessment remotely. Whilst working as Level 2 paediatric registrars, we organised small group bedside teaching locally within our West of Scotland deanery. This provided guidance on clinical exam technique (including general physical assessment and history-taking), alongside more subspecialised paediatric exposure. We rapidly adapted and expanded the existing teaching programme to support trainees with preparation for the new virtual MRCPCH clinical exam during the COVID-19 pandemic. Methods: Paediatric trainees faced lack of opportunity to practise clinical examination skills through traditional bedside teaching and face-to-face communication sessions. We identified all junior trainees (ST1 – ST3) within the West of Scotland deanery who were planning to sit either the upcoming or subsequent exam diet and created a virtual teaching programme commencing 6-weeks prior to the examination period. We contacted both general and subspeciality paediatric registrars/consultants requesting their participation in delivering virtual teaching sessions via our MS Teams channel. Results: A range of subspecialties were covered throughout the teaching programme including: cardiology, respiratory, neurology, rheumatology, nephrology, endocrine and child development (incorporating the clinical examination curriculum). Simulated paediatric and neonatal communication sessions provided opportunity for trainees to practise alongside each other within exam timings, whilst receiving constructive feedback. In addition to our own West of Scotland trainee cohort, junior paediatricians from 3 other Scottish deaneries have also accessed the programme. Subspecialty registrars from other regions additionally offered sessions. Following completion of the first virtual teaching programme a standardised questionnaire with invitation for open comments was sent to each participant and returned anonymously. Review of feedback has enabled programme modification to benefit future trainees. 100% of respondents would recommend the programme to other trainees, whilst 90% rated the standard as 'excellent' and 10% as 'very good' – descriptors used included: 'incredible', 'invaluable' and 'genuinely fantastic'. Candidates were reassured by coordinators' being 'in constant communication' with them and appreciated the 'wide variety' of subspecialties and 'realistic scenarios' covered by presenters. Conclusion: Lack of equality in opportunity to practise clinical examination skills or gain paediatric subspecialty exposure have been longstanding issues. Virtual teaching of clinical technique and communication skills is feasible; it also permits greater trainee attendance as compared to face-to-face sessions, whilst increasing exposure to specialist subjects (in particular for those on district general placements). Challenges encountered included candidates struggling to attend planned teaching sessions due to pre-existing clinical commitments and difficulty engaging busy subspecialty clinicians in the programme. Delivery of a virtual teaching programme was felt to be both accessible and beneficial for paediatric trainees remotely sitting the COVID-adapted MRCPCH clinical exam.